Determinasi Cash Holding melalui Investasi, Dividen, Aset Berwujud, dan Kepemilikan Institusional - Febriana Louw (Yayasan Literasi Sains Indonesia, 2025)
Cash management plays a critical role for companies in the consumer non-cyclicals sector, as cash supports operational activities, investment needs, and shareholder obligations. However, cash policies vary across firms, making it important to identify the determinants of cash holding. This study aims to analyse the effects of asset tangibility, capital expenditure, dividend payout ratio, and institutional ownership on cash holding in consumer non-cyclicals companies listed on the Indonesia Stock Exchange. The study employs a quantitative approach with an associative research design. A purposive sampling technique was used to select 27 firms that consistently distributed dividends during 2019–2023, resulting in 135 firm-year observations. Data processing was carried out using multiple linear regression analysis through EVIEWS-12 to examine the relationships among the variables. The results indicate that asset tangibility and institutional ownership have a negative and significant effect on cash holding, while the dividend payout ratio has a positive and significant effect on cash holding. Conversely, capital expenditure exhibits no significant effect. These findings highlight that cash policy is shaped not only by financial characteristics but also by ownership structure. This study contributes empirically by providing insights for companies in formulating liquidity strategies aligned with financial decisions and governance considerations.